Peningkatan Efisiensi Penyimpanan Logistik pada Warehouse Raw Material di PT Indofood Fortuna Makmur - Rahmayanti, Dina; Dongoran, Ihsan Wajhiya Siregar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research was conducted in the raw material warehouse division of PT Indofood Fortuna Makmur, a snack food manufacturing company known for products such as Chitato, Chiki, and Qtela, located in Cikupa, Tangerang. The objective of the study is to evaluate and improve the effectiveness and efficiency of the warehouse management system, particularly in addressing operational challenges due to increased production capacity and the use of temporary rental storage at Warehouse 88. The data were analyzed using the 5S method, ABC analysis, and seasonal slotting. The implementation of the 5S principles proved to improve orderliness, cleanliness, and workplace safety. The seasonal slotting method helped optimize raw material storage by adjusting locations based on seasonal production patterns. Meanwhile, ABC analysis enabled more efficient and structured stock and storage space management. The integration of these three methods significantly enhanced the overall performance of the warehouse system at PT Indofood Fortuna Makmur.